Energy in Biothermodynamics: A Comprehensive Review (Comprehensive Journal of Science, 2025)
This review investigates the application of thermodynamic principles to biological systems,emphasizing the human body as a model of an open, self-regulating system. It explores similaritiesand differences between living organisms and classical thermal machines. The human bodycontinuously transforms chemical energy into mechanical and thermal work, following the samephysical laws that govern inanimate systems. By analyzing energy conversion, entropy, andefficiency, this paper demonstrates how thermodynamic principles can deepen our understanding ofphysiological processes and inspire advancements in medical technology .
Keywords: Biothermodynamics; Human body; Thermodynamic laws; Energy conversion; Metabolism; Entropy